2014
DOI: 10.4995/wrs.2014.2105
|View full text |Cite
|
Sign up to set email alerts
|

The effect of unilateral ovariectomy on early embryonic survival and embryo development in rabbits

Abstract: Unilateral ovariectomy can be used to study uterine capacity in rabbits because an overcrowding of the functional uterine horn is produced. Due to the uterus duplex, the rabbit is the ideal model for such studies. However, this technique may affect embryo survival. The aim of this work is to study the effect of unilateral ovariectomy on early embryo survival and development in rabbit. A total of 101 unilateral ovariectomised females and 52 intact females were compared after slaughter at 30 h post-mating. Early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…However, comparing both groups, Synthetic line showed a lower percentage of normal embryos (95 vs. 98%) and a higher percentage of abnormal embryos (5 vs. 2%). It appears that an increasing ovulation rate is accompanied by an increase in number of abnormal embryos due to decreasing quality of oocytes, which is in agreement with other studies (Angel et al, 2014;Peiró et al, 2014). In fact, it has been shown that embryonic losses, number of oocytes and degenerated embryos are increased as ovulation rate rises (Angel et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…However, comparing both groups, Synthetic line showed a lower percentage of normal embryos (95 vs. 98%) and a higher percentage of abnormal embryos (5 vs. 2%). It appears that an increasing ovulation rate is accompanied by an increase in number of abnormal embryos due to decreasing quality of oocytes, which is in agreement with other studies (Angel et al, 2014;Peiró et al, 2014). In fact, it has been shown that embryonic losses, number of oocytes and degenerated embryos are increased as ovulation rate rises (Angel et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Litter size is limited by several components of traits such as ovulation rate, fertilisation and prenatal mortality (see review in Blasco et al, 1993a). Fertilisation rate is generally high, exceeding 90 to 95% (Peiró et al, 2014), and is therefore not considered a constraining component of litter size (Belabbas et al, 2016). However, ovulation rate is, together with pre and postimplantation mortality, the foremost component of litter size, and is also a limiting factor for its improvement (Laborda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, ovulation rate is, together with pre and postimplantation mortality, the foremost component of litter size, and is also a limiting factor for its improvement (Laborda et al, 2011). Preimplantation losses are mainly related to the embryo's viability related to chromosomal abnormalities, oocyte quality or embryonic development (Fechheimer and Beatty, 1974;Pope et al, 1990) and to the quality of oviduct and uterine secretions (Peiró et al, 2014). After implantation, the losses are related to the placenta development and uterine capacity of the female (Argente et al, 2003…”
Section: Introductionmentioning
confidence: 99%
“…In rabbits, no differences were observed in either embryo quality or survival rates between intact and unilaterally ovariectomised females (Peiro et al 2014 ). This suggested that unilateral ovariectomy was not associated with any physiological or hormonal imbalance leading to increased embryo loss (Peiro et al 2014 ). It further suggested that fertility in various species is apparently unaffected by unilateral ovariectomy.…”
Section: Introductionmentioning
confidence: 99%